2023
DOI: 10.1021/acs.jcim.3c00643
|View full text |Cite
|
Sign up to set email alerts
|

Open-Source Machine Learning in Computational Chemistry

Abstract: The field of computational chemistry has seen a significant increase in the integration of machine learning concepts and algorithms. In this Perspective, we surveyed 179 open-source software projects, with corresponding peer-reviewed papers published within the last 5 years, to better understand the topics within the field being investigated by machine learning approaches. For each project, we provide a short description, the link to the code, the accompanying license type, and whether the training data and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 350 publications
(639 reference statements)
0
4
0
Order By: Relevance
“…In addition to structural proteins, it was found that DeepKa is applicable to intrinsically disordered peptides (IDPs), such as NUPR1, sharing high robustness with a physics model like CpHMD . DeepKa is open access and recommended by Alexander Hagg and Karl N. Kirschner in their recent perspective article of open-source machine learning in computational chemistry …”
Section: Introductionmentioning
confidence: 99%
“…In addition to structural proteins, it was found that DeepKa is applicable to intrinsically disordered peptides (IDPs), such as NUPR1, sharing high robustness with a physics model like CpHMD . DeepKa is open access and recommended by Alexander Hagg and Karl N. Kirschner in their recent perspective article of open-source machine learning in computational chemistry …”
Section: Introductionmentioning
confidence: 99%
“…21–24 Although ML models are still not a complete substitute for expert intuition, 25 they are sufficiently sophisticated to recognize complex patterns beyond the reach of expert intuition to provide decision-making advice for major challenges in science and engineering, as multiple algorithms and different architectures for ML solutions emerge. 26–29…”
Section: Introductionmentioning
confidence: 99%
“…Computer-aided chemistry has taken many forms in recent decades. The use of machine learning (ML) has proliferated in order to drastically reduce design and experimental effort [28][29][30]. Therefore, there is an urgent need to bypass traditional tedious experimental exploration and theoretical calculation processes and combine emerging ML methods with luminescent chemistry to achieve rapid and accurate predictions of luminescent properties from their molecular structures [31][32][33].…”
Section: Introductionmentioning
confidence: 99%